2019
DOI: 10.1021/acsami.9b12961
|View full text |Cite
|
Sign up to set email alerts
|

Strengthened Perovskite/Fullerene Interface Enhances Efficiency and Stability of Inverted Planar Perovskite Solar Cells via a Tetrafluoroterephthalic Acid Interlayer

Abstract: In this work, a novel back contact interface engineering is developed for inverted planar perovskite solar cells, in which a tetrafluoroterephthalic acid (TFTPA) interlayer is inserted between CH 3 NH 3 PbI 3 and PC 61 BM to strengthen the interface contact. Benefiting from the strong Coulombic interactions between positive electron-poor tetrafluoroterephthalate moieties and negative electron-rich fullerene molecules, as well as the coordinate effect between −COOH groups of TFTPA and Pb 2+ ions of perovskites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…16 Therefore, interfacial stabilization at the interface of PVK/ETL is crucial for achieving both high efficiencies and long-term stabilities in inverted p-i-n PSCs. While the performance improvements have been demonstrated by various approaches, 3,6,,13,15,17-22 including the use of different inorganic 13,17 or organic 15,[18][19][20] interfacial layers between PVK and C60, further performance improvements are still needed to bring these devices closer to commercialization. 7 Here we use a boron chloride subphthalocyanine (Cl6SubPc)/fullerene ETL to simultaneously reduce the interfacial defect density and hinder ion migration, resulting in power conversion efficiencies of 22.0% (certified 21.3 %), a shelf life of 7000 hours, T80 of 816 h under damp heat stress, and performance retention of 98% after 2000 hours at 80 o C in inert environment, and 95% after 1200 h outdoor testing (first outdoor performance test for inverted devices).…”
Section: Introductionmentioning
confidence: 99%
“…16 Therefore, interfacial stabilization at the interface of PVK/ETL is crucial for achieving both high efficiencies and long-term stabilities in inverted p-i-n PSCs. While the performance improvements have been demonstrated by various approaches, 3,6,,13,15,17-22 including the use of different inorganic 13,17 or organic 15,[18][19][20] interfacial layers between PVK and C60, further performance improvements are still needed to bring these devices closer to commercialization. 7 Here we use a boron chloride subphthalocyanine (Cl6SubPc)/fullerene ETL to simultaneously reduce the interfacial defect density and hinder ion migration, resulting in power conversion efficiencies of 22.0% (certified 21.3 %), a shelf life of 7000 hours, T80 of 816 h under damp heat stress, and performance retention of 98% after 2000 hours at 80 o C in inert environment, and 95% after 1200 h outdoor testing (first outdoor performance test for inverted devices).…”
Section: Introductionmentioning
confidence: 99%
“…For reference, V bi values were calculated with the following equation: C −2 = 2( V bi − V )( A 2 eεε o N A ) −1 , where A is the active device area and N A is the doping concentration. [ 37,38 ]…”
Section: Resultsmentioning
confidence: 99%
“…where A is the active device area and N A is the doping concentration. [37,38] Meanwhile, the organic HTMs have strong absorption in UV region, and this is beneficial to block the UV light that can degrade perovskite layer. X-ray diffraction (XRD) patterns in Figure 4e show that PbI 2 -related peaks are generated from the perovskite prepared on ITO/bare NiO x after 12 h continuous UV light-illumination (365 nm, 15 mW cm −2 , and illumination .…”
Section: Perovskite Pv Cell Performances With Organic Hole Transport mentioning
confidence: 99%
“…Organic materials with long alkyl chains or other hydrophobic groups could restrict the ingress of moisture. [129][130][131][132] The shielding effect can be further enhanced when conjugated and cross-linked polymers with network structures are used, which can prevent the outward ion diffusion from perovksite. [133][134][135][136] One important advantage of organic materials is their flexibility, which is benefit for the formation of compact wrapping layer around perovskites.…”
Section: Organic Barriersmentioning
confidence: 99%
“…After storage of 30 days at RT in a 30% RH condition, the controlled device kept 78% of the initial PCE while the TFTPA based device still retained 92% of its initial efficiency. [132] Huang et al introduced a poly(ethylene-co-vinyl acetate) (EVA) glued layer between www.advancedsciencenews.com MAPbI 3 and PCBM as barrier layer to improve the interfacial contact and also to improve the resistance of perovskite against moisture and ion diffusion ( Figure 4h). [135] It was found that perovskite with EVA presented superior hydrophobicity, with a contact angle of ≈103.6°, remarkably larger than the pristine one (≈72.5°).…”
Section: Organic Barriers Between Perovskites and Ctlsmentioning
confidence: 99%